Remodeling extracellular matrix based on functional covalent organic framework to enhance tumor photodynamic therapy. (March 2020) - Wang, Shi-Bo; Chen, Zhao-Xia; Gao, Fan; Zhang, Cheng; Zou, Mei-Zhen; Ye, Jing-Jie; Zeng, Xuan; Zhang, Xian-Zheng
Abstract: Photodynamic therapy (PDT) is a promising treatment modality for tumor suppression. However, the hypoxic state of most solid tumors might largely hinder the efficacy of PDT. Here, a functional covalent organic framework (COF) is fabricated to enhance PDT efficacy by remodeling the tumor extracellular matrix (ECM). Anti-fibrotic drug pirfenidone (PFD) is loaded in an imine-based COF (COFTTA-DHTA ) and followed by the decoration of poly(lactic-co-glycolic-acid)-poly(ethylene glycol) (PLGA-PEG) to fabricate PFD@COFTTA-DHTA @PLGA-PEG, or PCPP. After injected intravenously, PCPP can accumulate and release PFD in tumor sites, leading to down-regulation of ECM compenents such as hyaluronic acid (HA) and collagen I. Such depletion of tumor ECM reduces the intratumoral solid stress, a compressive force exerted by the ECM and cells, decompresses tumor blood vessels, and increases the density of effective vascular areas, resulting in significantly improved oxygen supply in tumor. Furthermore, PCPP-mediated tumor ECM depletion also enhances the tumor uptake of subsequently injected Protoporphyrinl IX (PPIX)-conjugated peptide formed nanomicelles (NM-PPIX) due to the improved enhanced permeability and retention (EPR) effect. Both the alleviated tumor hypoxia and improved tumor homing of photosensitizer (PS) molecules after PCPP treatment significantly increase the reactive oxygen species (ROS) generation in tumor and therefore realize greatly enhanced PDT effect of tumor in vivo. Graphical abstract: A covalent organic framework (COF)-based nanosystem PCPP was fabricated to enhance tumor photodynamic therapy (PDT). PCPP can trigger the depletion of tumor extracellular matrix (ECM), leading to improved oxygen supply as well as photosensitizer uptake in tumor to achieve enhanced tumor PDT. Image 1